INTEGRASI NILAI-NILAI FIQIH MUAMALAH DALAM PEMBELAJARAN PENDIDIKAN AGAMA - Mahfud Sidik; Dede Saepul Bahri; Rifai Yusuf; Alam Tarlam (Program Studi Pendidikan Agama Islam UNU Purwokerto, 2025)
Abstrak: This article aims to analyze the correlation between Fiqih Muamalah and the development of contextual Pendidikan Agama Islam (PAI). Amid rapid socio-economic dynamics, it is crucial for PAI instruction to incorporate the principles of Fiqih Muamalah so that students can internalize values such as justice, honesty, and responsibility in community life. Using a descriptive qualitative approach, this study highlights the importance of integrating Islamic commercial jurisprudence with pedagogical practice and its relevance in shaping religious and moderate student character.